Aquatic macrophytes drive sediment stoichiometry and the suspended particulate organic carbon composition of a tropical coastal lagoon - Marinho,Cláudio Cardoso (2010)
AIM: This research aimed to evaluate (1) the influence of the aquatic macrophytes Typha domingensis Pers., Eleocharis interstincta (Vahl) Roem. & Schult. (emergent) and Potamogeton stenostachys K. Schum. (submersed) on sediment stoichiometry and (2) the contribution of these aquatic macrophytes to organic carbon composition in different compartments of a tropical coastal lagoon (Cabiúnas Lagoon, Macaé-RJ); METHODS: The concentration of carbon (C), nitrogen (N) and phosphorus (P) was determined in 2-cm intervals in the first 10 cm of sediment in both littoral and limnetic regions. In the littoral region, the sediment was collected in three different sites: T. domingensis, E. interstincta and P. stenostachys stands. In order to know the pathways of C in Cabiunas lagoon, the isotopic signature (δ13C) of restinga terrestrial vegetation, zooplankton, phytoplankton, macrophytes, dissolved and suspended material on water were evaluated; RESULTS: The concentrations of C and N in the sediment of the E. interstincta and T. domingensis stands were significantly higher than in the sediment of the limnetic region. The concentration of phosphorus in the sediment colonized by T. domingensis was higher than in the limnetic region and in P. stenostachys stand. The highest molar C:P ratios were found in E. interstincta and P. stenostachys stands. The highest N:P ratios were also found in the littoral region. Carbon stable isotopic analysis (δ13C signatures) showed that a majority of the particulate organic carbon (POC) in the water column had aquatic macrophyte tissues origin; CONCLUSIONS: Emergent macrophytes strongly contribute to nutrient enrichment of the sediment of Cabiúnas lagoon. In general, macrophyte detritus alters the littoral region sediment stoichiometry and quality for decomposers, by accumulating much more C in relation to N and P when compared to limnetic region. However, macrophytes importance isn't restricted to the sediment once they have a central role in the composition of suspended POC, thus representing an important coupling between compartments in this lagoon.